Community Acceptance of New Criminal Law Policies in Cases of Violence - Arianti, Fitri (PT. Anagata Sembagi Education, 2025)
This research aims to explore public acceptance of new criminal law policies applied in handling cases of violence in Indonesia. With a qualitative approach, the study used in-depth interviews and focus group discussions to collect data from different walks of life, including victims of violence, perpetrators, law enforcement, and members of the general public. The results show that while there has been positive reception for increased sanctions and legal reforms aimed at protecting victims, there are concerns about the implementation and consistency of law enforcement. Many respondents expressed the need for better education and social support to ensure that the policy is effective in practice. These findings provide important insights into how new policies are accepted on the ground and what obstacles are faced in the implementation process. This research is expected to be a reference for policymakers and legal practitioners in formulating more effective strategies in handling cases of violence in the future